Brassinosteroids Regulate Anthocyanin Biosynthesis in the Ripening of Grape Berries - Luan, L.-Y.; Zhang, Z.-W.; Xi, Z.-M.; Huo, S.-S.; Ma, L.-N. (South African Journal of Enology and Viticulture, 2016)
Anthocyanins are important components in the skins of grapes and in the development of wine colour. Various environmental factors cause poor coloration in some areas, even for the same cultivars planted in different production areas. The objective of this study was to evaluate the effect of exogenous brassinosteroids (BR) on the accumulation of anthocyanins and gene expression of anthocyanin biosynthesis in wine grape berry skins. The results show that total anthocyanin content in BR-treated grapes was higher than that in the control (CT) grapes, and that 0.4 mg/L was the most effective treatment concentration. The effect of BR on downstream genes was more effective than that on upstream genes. Full coloration of BR-treated grapes was achieved seven days earlier than in the case of CT. Moreover, BR enhanced the transcript level of the downstream genes of anthocyanin biosynthesis, which caused the total anthocyanin content to increase. The induction of structural and regulatory genes of the flavonoid pathway suggests that the interrelationships between developmental and environmental signalling pathways were magnified by BR treatment, which actively promoted fruit coloration, namely anthocyanin biosynthesis.